Pengaruh Heat Moisture Treatment Menggunakan Microwave dengan Penambahan Gliserol Terhadap Karakteristik Fisikokimia Tapioka - Kelirey, Rudi; Polnaya, Febby J; Palijama, Syane (Jurnal Agrosilvopasture-Tech, 2025)
This study investigated the effect of glycerol concentration on the physicochemical properties of tapioca starch modified through heat–moisture treatment (HMT) using microwave heating. Glycerol was incorporated at concentrations of 5% (HMTg5), 10% (HMTg10), and 15% (HMTg15) based on the dry weight of tapioca starch, with conventional HMT-modified starch serving as the control. The experiment was conducted using a completely randomized design with a non-factorial structure. The analyzed physicochemical parameters included ash content, water absorption capacity, oil absorption capacity, swelling power, solubility, bulk density, and whiteness index. The results revealed that the water and oil absorption capacities of HMTg starches were significantly higher than those of the control HMT starch. In contrast, ash content, swelling power, solubility, bulk density, and whiteness index decreased with increasing glycerol concentration. These findings suggest that incorporating glycerol during HMT modification alters the starch granule structure and intermolecular interactions, resulting in improved water and oil affinity while reducing swelling and solubility. The modified starches produced in this study demonstrate promising potential for food processing applications and as functional ingredients in biodegradable polymer formulations.